Self-Care of African Immigrant Adults with Chronic Illness. (March 2022) - Osokpo, Onome Henry; Lewis, Lisa M.; Ikeaba, Uchechukwu; Chittams, Jesse; Barg, Frances K.; Riegel, Barbara
This cross-sectional study aims to describe the self-care of adult African immigrants in the US with chronic illness and explore the relationship between acculturation and self-care. A total of 88 African immigrants with chronic illness were enrolled. Self-care was measured with the Self Care of Chronic Illness Inventory v3 and the Self-Care Self-Efficacy scale. Scores are standardized 0 to 100 with scores >70 considered adequate. Acculturation was measured using a modified standardized acculturation instrument and predefined acculturation proxies. The self-care scores showed adequate self-care, with the mean scores of 78.6, 77.9, and 75.6 for self-care maintenance, monitoring, and management. Self-care self-efficacy mean score was 81.3. Acculturation was not significantly associated with self-care. Self-care self-efficacy was a strong determinant of self-care maintenance ( p  < .0001), monitoring ( p  < .0001), and management ( p  < .0001). The perception of inadequate income was a significant determinant of poor self-care management ( p  = .03). Self-care self-efficacy and perceived income adequacy were better determinants of self-care than acculturation.